How Stable Ischemic Heart Disease Leads to Acute Coronary Syndrome in COVID-19? - Shafeghat, Melika; Aminorroaya, Arya; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2021)
Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, the increased mortality risk of patients with underlying cardiovascular diseases and COVID-19 was raised. Besides, coronavirus itself enhances the incidence of myocardial injury, which suggests a two-sided relation. We aimed to discuss the role of COVID-19 in the progression of stable coronary artery disease (CAD) to acute coronary syndrome (ACS), which might lead to a greater rate of out-of-hospital cardiac arrest and a higher fatality rate of ACS during the pandemic. We briefly reviewed several mechanisms in this regard: Systemic inflammation and cytokine release in critical patients; Plaque rupture and coronary thrombosis; Dysregulation of cytotoxic T-cell lymphocytes; Malignant ventricular arrhythmias. We reinforce applying more attention to COVID-19 patients with stable CAD during follow-up to prevent progression to ACS. These individuals should seriously observe World Health Organization protocols to avoid virus transmission by carriers.